Implementasi Progressive Web Apps (PWA) Menggunakan Laravel Dan Vue.Js dalam Pembuatan Aplikasi Penyedia Jasa Freelance - Adriyansah Efendi Noor; Pahrul Irfan (JTIM : Jurnal Teknologi Informasi dan Multimedia, 2020)
Vocational High School or in Indonesian abbreviated as SMK, is a government program that was built with the aim that students can have expertise in certain fields and can be the initial capital for them in looking for work. An accredited educational curriculum and the many practical activities provided to students can also ensure that SMK graduates are ready to enter the workforce. However, in today's world of work, it requires workers who, in addition to having skills, must also have work experience. There are events held by the government regarding Job Vacancy info which are held only a few times a year so that more participants are participating and the unemployment rate in the regions is getting higher. Based on the above problems, the authors provide a solution by creating a "Freelance Service Provider Application" which is expected to bring together workers and job seekers. The application is made web-based so that it can be easily accessed through various types of devices. The author also implements Progressive Web Apps technology or also known as PWA so that it can be more easily accessed on mobile devices. Based on the results of the discussion on the implementation of PWA technology for making applications for freelance service providers, this can be a means for the public and prospective workers to meet and conduct transactions. So based on the questionnaire data obtained from the respondents, it can be concluded that the research carried out was successful and it is felt that it can help the graduates of SMK 3 Mataram to get jobs and also work experience